Reduced discomfort during high-definition transcutaneous stimulation using 6% benzocaine - Guleyupoglu, Berkan; Febles, Nicole; Minhas, Preet; Hahn, Christoph; Bikson, Marom (Frontiers in Neuroengineering, 2014)
Background: High-Definition transcranial Direct Current Stimulation (HD-tDCS) allows for non-invasive neuromodulation using an array of compact (approximately 1 cm2 contact area) “High-Definition” (HD) electrodes, as compared to conventional tDCS (which uses two large pads that are approximately 35 cm2). In a previous transcutaneous study, we developed and validated designs for HD electrodes that reduce discomfort over >20 min session with 2 mA electrode current. Objective: The purpose of this study was to investigate the use of a chemical pretreatment with 6% benzocaine (topical numbing agent) to further reduce subjective discomfort during transcutaneous stimulation and to allow for better sham controlled studies. Methods: Pre-treatment with 6% benzocaine was compared with control (no pretreatment) for 22 min 2 mA of stimulation, with either CCNY-4 or Lectron II electroconductive gel, for both cathodal and anodal transcutaneous (forearm) stimulation (eight different combinations). Results: Results show that for all conditions and polarities tested, stimulation with HD electrodes is safe and well tolerated and that pretreatment further reduced subjective discomfort. Conclusion: Pretreatment with a mild analgesic reduces discomfort during HD-tDCS.